Assessing Disease Activity in Pediatric Crohn's Disease Using Ultrasound: The Pediatric Crohn Disease Intestinal Ultrasound Score. Issue 5 (7th February 2023) - van Wassenaer, Elsa A.; van Rijn, Rick R.; de Voogd, Floris A.E.; van Schuppen, Joost; Kindermann, Angelika; de Meij, Tim G.J.; van Limbergen, Johan E.; Gecse, K.B.; D'Haens, Geert R.; Benninga, Marc A.; Koot, Bart G.P.
Abstract : Objectives: Currently, there is no consensus on how to score Crohn disease (CD) activity assessed by intestinal ultrasound (IUS) in children. This study aimed to design an easy-to-use IUS score for disease activity in pediatric CD. Methods: Children undergoing ileo-colonoscopy for CD assessment underwent IUS the day before ileo-colonoscopy, assessed with simple endoscopic score for CD (SES-CD). IUS features were compared to the SES-CD on segmental level. Multiple regression analyses, separately for terminal ileum (TI) and colon, were done to assess predictors of disease activity and to develop a model. Results: In 74 CD patients (median 15 years, 48% female), 67 TI and 364 colon segments were assessed. Based on receiver operating characteristics curves, bowel wall thickness (BWT) was categorized into low [1 point: 2–3 mm (TI) and 1.6–2 mm (colon)], medium [2 points: 3.0–3.7 mm (TI) and 2.0–2.7 mm (colon)], and high [3 points: >3.7 mm (TI) and >2.7 mm (colon)]. In TI, only BWT was retained in the model [high BWT: odds ratio (OR) 11.50, P < 0.001]. In colon, BWT (high BWT: OR 8.63, P < 0.001) and mesenteric fat (1 point: OR 3.02, P < 0.001) were independent predictors. A pediatric Crohn disease IUS score (PCD-US) cut-off of 1 resulted in a sensitivity of 82% (95% confidence interval, CI: 65%–93%) and 85% (95% CI: 80%–89%) and a cut-off of 3 in a specificity of 88% (72%–97%) and 92% (87%–96%) for TI and colon, respectively. Inter-observer agreement was moderate for TI and colon ( K : 0.42, K : 0.49, respectively). Conclusions: The PCD-US score is an easy-to-use and reliable score to detect or rule out CD activity on segmental level in children. External validation is needed before applying this score in clinical practice.